2019
DOI: 10.1111/1475-6773.13138
|View full text |Cite
|
Sign up to set email alerts
|

Postacute care outcomes and medicare payments for patients treated by physicians and advanced practitioners who specialize in nursing home practice

Abstract: Objective To measure the association between clinician specialization in nursing home (NH) practice and outcomes of patients who received postacute care in skilled nursing facilities (SNFs). Data Sources Medicare claims and NH assessments for 2 118 941 hospital discharges to 14 526 SNFs in January 2012‐October 2014 and MD‐PPAS data for 52 379 clinicians. Study Design Generalist physicians and advanced practitioners with ≥ 90 percent of claims for NH‐based care were considered NH specialists. The primary clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…For example, prior evidence supports the use of advanced practitioners in nursing homes, 13 as well as physicians who specialize in nursing home practice. 14 We also need to understand the effects of public reporting of COVID-19 cases and deaths, as well as COVID-related funding penalties, on the quality of and access to nursing home and residential caredincluding facility closures. Fiscally vulnerable facilitiesdfacilities that mainly house Medicaid residents, operate on narrow financial margins, and have limited resourcesdmay be disproportionally affected by the recently issued CMS penalties for infection control lapses.…”
Section: Implications For Practice Policy and Researchmentioning
confidence: 99%
“…For example, prior evidence supports the use of advanced practitioners in nursing homes, 13 as well as physicians who specialize in nursing home practice. 14 We also need to understand the effects of public reporting of COVID-19 cases and deaths, as well as COVID-related funding penalties, on the quality of and access to nursing home and residential caredincluding facility closures. Fiscally vulnerable facilitiesdfacilities that mainly house Medicaid residents, operate on narrow financial margins, and have limited resourcesdmay be disproportionally affected by the recently issued CMS penalties for infection control lapses.…”
Section: Implications For Practice Policy and Researchmentioning
confidence: 99%
“…In a national study of facilities with both types of clinicians, patients under the care of SNFists had 1.5% lower rehospitalization rate and 0.8% higher rate of successful discharge to community [10]. However, patients of SNFists experienced higher Medicare payments during the sixty days following hospital discharge, compared to patients of physicians who did not specialize in SNF practice [10]. Little is known about patient and caregiver experiences and perceptions of SNFist care.…”
Section: Snfs After a Hospitalization Poor And Incomplete Communicatmentioning
confidence: 99%
“…There is evidence that patients under the care of SNFists have better outcomes. In a national study of facilities with both types of physicians, patients under the care of SNFists had 1.5% lower rehospitalization rate and 0.8% higher rate of successful discharge to community [10]. Little is known about patient and caregiver experiences and perceptions of SNFist care.…”
Section: Strati Ed Analysesmentioning
confidence: 99%
“…Some physicians and nurse practitioners are increasingly focusing their practice exclusively on treating patients in these facilities (colloquially known as "SNFists") [7][8][9]. Although one study using Medicare data found that patients under the care of SNFists have slightly better clinical outcomes [10], it did not evaluate patient perceptions of their care.…”
Section: Introductionmentioning
confidence: 99%